Судьба авторитета в современном мире - Бурлачук, В. (Социология: теория, методы, маркетинг, 2000)
The establishment of democratic power institutions has caused the substitution of anonymous kind of power for that of totalitarianism. Studying crisis as a process of the established world order disintegration sets the task of elucidating the effect of the social mechanisms which participate in preserving the social reality and prevents its complete disorientation. Authority, as well as tradition, should be used to curb the elemental forces which have gone out of the social control, and offer an individual a set of values, emotional orientations, rules and standards of behavior which can become the means of achieving social peace.